Influence Of HIV/AIDS Policy Implementation Factors on The Performance Of Aids Commission (KPA) In Nabire Regency - Manggo, Beatrix Antoneta (Advances in Social Sciences Research Journal, 2021)
Papua Province comes first nationally with the highest number of HIV/AIDS cases in Indonesia. Meanwhile at the provincial level, Nabire Regency has the highest number of HIV and AIDS cases. The HIV epidemic in Nabire Regency is classified as a generalized epidemic with the highest prevalence of cases among women, which is said to be the highest in Papua Province. The problem of HIV / AIDS is not only a health problem, but also a social problem that needs to be addressed. This has led to the formulation of public policies in the form of HIV / AIDS prevention policies. The establishment of AIDS Commission in Nabire Regency (KPAK Nabire) is one of the government’s efforts to involve the general public in helping to tackle HIV / AIDS cases in Nabire Regency. In connection with the phenomenon of the problem at hand, this study aims to analyze the influence of policy implementation factors on organizational performance. This study applied primary data obtained through questionnaires with a final sample of 80 respondents. Data analysis was done to describe the variables using SPSS Statistics, to evaluate the research model using the SEM (Structural Equation Modeling) technique, and to test the mediation effect using the Sobel test. The results showed that only resource factors, bureaucratic structure, communication and disposition of the implementors that directly and indirectly influence the performance of KPAK Nabire. Meanwhile, environmental conditions did not affect the performance of KPAK Nabire. The implementor disposition mediates the influence of the factors of policy implementation on organizational performance. The analysis results also show that disposition of the implementor is the most dominant predictor of KPAK Nabire’s performance.